Large-area plasmonic electrodes and active plasmonic devices generated by electrochemical processes. (10th October 2015) - Nguyen, Van-Quynh; Schaming, Delphine; Martin, Pascal; Lacroix, Jean-Christophe
Graphical abstract: Abstract: This work describes a fast electrodeposition method for generating gold plasmonic electrodes and their use as active plasmonic devices. Gold nanoparticles (AuNPs) are easily obtained on large areas (up to several square centimeters) on indium tin oxide (ITO) electrodes using electroreduction of an Au III salt by chronoamperometry. These AuNP substrates exhibit a strong localized surface plasmon resonance (LSPR) signal in the visible range, and constitute low-cost plasmonic electrodes. The average size, the density and the dispersity of the AuNPs, as seen by scanning electron microscopy (SEM), can be modulated by the potential applied during electroreduction. In this way, the LSPR can be varied from 680 nm to 580 nm with a concomitant marked evolution of the full-width at half-maximum from 200 to 80 nm. An important result is that the LSPR of substrates generated at −0.9 V using a charge density of 20 mC cm −2 is close to that of AuNP gratings obtained using e-beam lithography. In a second step, the best AuNP-modified electrodes were covered with an ultrathin organic film of bisthienylbenzene (BTB) generated by electroreduction of the corresponding diazonium salt. This film switches between a conducting and an insulating state depending on the applied voltage. The effect of the switch on the plasmonic properties of AuNPs is reported. Despite the small thickness of the film (below 15 nm), its conductance switch leads to a reversible modulation of the LSPR intensity by as much as 25%.